An Analysis of Figurative Language in Cnn International News Headlines Post on Facebook - Sergius Kasma; Ni Made Verayanti Utami; I Gusti Agung Sri Rwa Jayantini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
Abstract This study aims to analyze the figurative language found in CNN news headlines, especially about the types and meanings of figurative language that contained in headlines of CNN news. The problem that discussed in this study such as: what are the types of figurative language in CNN international news headline, and how the meaning of the figurative language that contained in CNN international news headline post on Facebook. Thus, in collecting the data the researcher used the descriptive qualitative method by doing several ways such as: reading news headlines, grouping news titles based to the figurative language type, write down the news headlines. As the result of this analysis the researcher found that are 5 types of figurative language in CNN. They are: Metonymy 2 or 40%, simile 1 or 20%, hyperbole 1 or 20%, and metaphor 1 20%. And the meaning as many as 3 meaning such as: conceptual meaning 3 or 60%, connotative meaning 1 or 20%, social meaning 1 or 20%. Keywords: Figurative Language, CNN International News, Headline.